Investigating the influence of ISIS radicalisation on the recruitment process: a critical analysis. Issue 2 (4th May 2019) - Tolis, Edoardo
ABSTRACT: Since June 2014 the world has been confronted by a new and alarming terrorist threat in the form of the Islamic State of Iraq and Syria (IS/ISIS). The intensification of the terrorist attacks perpetrated in Europe between the 2016 and 2017 by ISIS has placed terrorism at the top of the global agenda. This is not surprising as the Islamic State has recruited tens of thousands of fighters from around the globe. Considering the great appeal that ISIS has shown, policy makers, intelligence services as well as governments have been investigating what drives people to join ISIS. This article will investigate the influence of radicalisation on the recruitment process by analysing those factors that shape the pathway that lead people to join the Islamic State. Indeed, the hypothesis at the basis of this work is that the recruitment process indicates that efficient radicalisation has occurred.